Impact of Physical Education on Academic Performance and Mental Health: A review - Srinivasan, J. P. Desiga (AG Volumes, 2025)
It has long been held that understanding the relationship among mental health, academic achievement, and physical activity is essential to understanding human behaviour and growth. In this page, analyse the numerous studies that investigate the impact of physical education on academic achievement and mental health. This review emphasises how physical education has a major impact on students' emotional and intellectual well-being. Regular physical activity enhances focus, memory, and classroom behavior, leading to improved academic outcomes. It also mitigates mental health challenges like stress, anxiety, and depression while promoting vital life skills such as teamwork, leadership, and goal-setting. A lack of physical activity increases the risk of chronic diseases and can impair cognitive functions, such as attention and alertness. By fostering both physical well-being and emotional resilience, physical education plays a crucial role in developing healthier, more engaged, and well-rounded students equipped for academic and life success.